Predictors of Pain Reliever Misuse Among Respondents of the United States 2017 National Survey on Drug Use and Health - Marissa S Matta; Timothy P Janikowski (SAGE Publishing, 2022)
The risk factors for potential opioid misuse and abuse in patients receiving long-term opioid pain treatment have been a topic of interest in research for many years. There are differences among patients who receive long-term opioid pain treatment. These differences may or may not lead to opioid misuse. This study analyzes the different characteristics and predictors of prescription pain reliever misuse among respondents of the United States 2017 National Survey on Drug Use and Health. It examines the relationships of age, gender, income, perception of risk and availability of heroin, past substance use and alcohol use, the source of the pain relievers, and motivation to misuse pain relievers to pain reliever misuse and if these variables significantly predict pain reliever misuse. Data used in this study were analyzed through sequential multiple linear regression analyses. The significant positive predictors of prescription pain reliever misuse were being 26 or older, perceiving heroin as easily obtainable, and past methamphetamine use. The significant negative predictors of prescription pain reliever misuse were being 12 to 25 years old, perceiving heroin as a great risk, past alcohol use, and obtaining pain relievers from a friend or relative. The goal of this study was to increase the amount of knowledge regarding predictors of prescription opioid misuse to identify those who are at risk and decrease prescription opioid misuse and overdose rates in the United States.